Pengaruh Kompensasi dan Supervisi Akademik Terhadap Profesionalisme Guru Non-ASN Sekolah Dasar - Abdilah, Dahliana Asry; Herawan, Endang; bakar, Abu (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: Teacher professionalism is a crucial aspect in realizing quality education. The literature review indicates that teacher professionalism can be influenced by compensation and academic supervision. This study aims to prove: (1) the effect of compensation on the professionalism of non-ASN teachers in elementary schools in Astanaanyar Subdistrict, Bandung, and (2) the effect of academic supervision on the professionalism of non-ASN teachers in elementary schools in Astanaanyar Subdistrict, Bandung. Utilizing a case study type quantitative approach, a closed statement type questionnaire with a Likert scale model - was chosen as the data collection technique. This study successfully obtained responses from 127 participants who were designated as the research sample. The data analysis model used path analysis with AMOS software version 26 as a supporting tool. The results showed: (1) There is an influence of compensation on the professionalism of non-ASN teachers in elementary schools in Astanaanyar Subdistrict, Bandung (2) There is an influence of academic supervision on the professionalism of non-ASN teachers in elementary schools in Astanaanyar Subdistrict, Bandung. Taking into account the results of the study, to improve teacher professionalism in Indonesia, which is known not to have reached the expected level, we recommend the effective management of the compensation system through the determination of sanctions, and adequate academic supervision management so that academic supervision is guaranteed to function effectively. These findings can be interpreted in the context of other countries that are also implementing decentralized education systems. Finally, the discovery of other factors that may have implications for teacher professionalism is recommended as further research. Keywords: Teacher professionalism, Compensation, Academic supervision, Non-ASN teachers Abstrak: Profesionalisme guru merupakan aspek krusial dalam upaya mewujudkan pendidikan yang berkualitas. Tinjauan literatur mengindikasikan, bahwa profesionalisme guru dapat dipengaruhi oleh kompensasi dan supervisi akademik. Penelitian ini bertujuan untuk membuktikan: (1) Adanya pengaruh kompensasi terhadap profesionalisme guru non-ASN pada sekolah dasar di Kecamatan Astanaanyar, Bandung, dan (2) Adanya pengaruh supervisi akademik terhadap profesionalisme guru non-ASN pada sekolah dasar di Kecamatan Astanaanyar, Bandung. Memanfaatkan pendekatan kuantitatif tipe studi kasus, kuesioner tipe pernyataan tertutup dengan model skala Likert – dipilih sebagai teknik pengumpulan data. Penelitian ini berhasil memperoleh respon dari 127 partisipan yang ditetapkan sebagai sample penelitian. Model analisis data menggunakan path analysis dengan softwere AMOS versi 26 sebagai alat pendukung. Hasil penelitian menunjukkan: (1) Adanya pengaruh kompensasi terhadap profesionalisme guru non-ASN pada Sekolah Dasar di Kecamatan Astanaanyar, Bandung (2) Adanya pengaruh supervisi akademik terhadap profesionalisme guru non-ASN pada Sekolah Dasar di Kecamatan Astanaanyar, Bandung. Dengan mempertimbangkan hasil penelitian, untuk meningkatkan profesionalisme guru di Indonesia – yang diketahui belum mencapai level sesuai harapan, kami merekomendasikan efektivitas pengelolaan sistem kompensasi melalui penentuan sanksi, dan manajemen supervisi akademik yang memadai agar supervisi akademik terjamin berfungsi efektif. Temuan ini dapat diinterpretasikan ke dalam konteks negara lain yang turut menerapkan sistem desentralisasi pendidikan. Terakhir, upaya penemuan terhadap faktor-faktor lain yang dapat berimplikasi pada profesionalisme guru, sangat direkomendasikan sebagai penelitian lanjutan. Kata kunci: Profesionalisme guru, Kompensasi, Supervisi akademik, Guru non-ASN